A criação de um ambiente regulatório no Brasil: mecanismos de controle social e o processo de institucionalização das agências reguladoras federais - Komatsu, Suely (2004)
Recent changes in the Brazilian regulatory environment demand the creation of a new institutional context that allows to one better joint in the relation between State and society. The new experience based on the creation of “regulatory agencies” in Brazil evidences the deficiencies of its logic. This work, from revisions of the institutional and regulation theories, examines the sprouting and functioning of the current brazilian regulatory framework, especially the mechanisms of social control, and constructs a model that considers the interrelation enters the institucional dynamic of the spheres social and politics and, consequently, in one real public participation in the regulation process.